1995
DOI: 10.1007/bf00298378
|View full text |Cite
|
Sign up to set email alerts
|

Location by fluorescence microscopy of glycosidases and a xylanase in the anaerobic gut fungi Caecomyces communis, Neocallimastix frontalis, and Piromyces rhizinflata

Abstract: beta-D-Glucosidase, beta-D-fucosidase, beta-D-xylosidase, and beta-D-cellobiopyranosidase activities in Caecomyces communis, Neocallimastix frontalis, and Piromyces rhizinflata, located with fluorescent conjugates, occur throughout the whole thallus as from zoospore germination and disappear before sporulation. beta-D-Galactosidase and alpha-L-arabinopyranosidase activities are low or nonexistent. A xylanase, detected by indirect immunofluorescence, was observed at the surface of the vegetative cells, vesicles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…The anaerobic fungi produce a wide range of polysaccharide degrading enzymes. Enzymes have been found associated with the rhizomycelium and many were also secreted into the surrounding environment (Williams & Orpin, 1987;Lowe et al 1987d;Breton et al 1995;Gerbi et al 19963). The presence and activity of some surface associated enzymes have been shown to fluctuate according to the stage of the life cycle (Breton et at.…”
Section: Metabolismmentioning
confidence: 99%
“…The anaerobic fungi produce a wide range of polysaccharide degrading enzymes. Enzymes have been found associated with the rhizomycelium and many were also secreted into the surrounding environment (Williams & Orpin, 1987;Lowe et al 1987d;Breton et al 1995;Gerbi et al 19963). The presence and activity of some surface associated enzymes have been shown to fluctuate according to the stage of the life cycle (Breton et at.…”
Section: Metabolismmentioning
confidence: 99%
“…Carbohydrate active enzymes system in Caecomyces sp. Breton et al (1995) reported that Caecomyces sp. has the enzyme activity of β-glucosidase (EC 3.2.1.21), while β-galactosidase ( EC 3.2.1.23 related to the GH family) has no activity.…”
Section: Carbohydrate Active Enzymes System In Neocallimastix Spmentioning
confidence: 99%